Aripiprazole long-acting injection: promising but more evidence needed. (August 2016) - Keks, Nicholas A; Hope, Judy; Culhane, Christine
Objective: Aripiprazole long acting injection (ALAI) is now available, and this paper aims to assist clinicians in deciding when to use ALAI. Conclusion: Aripiprazole is a partial dopamine agonist with low sedation, relatively favourable metabolic profile and a tendency to lower, rather than raise, prolactin. Available for over a decade, aripiprazole has been increasingly recognised by many clinicians as a useful option in the treatment of psychoses. ALAI is a suspension of crystalline aripiprazole in water which takes 5–7 days to reach steady state after an initial intramuscular injection. Monthly injections achieve steady state in four months. Studies have demonstrated that ALAI is effective in aripiprazole-responsive patients. ALAI was generally well tolerated, but more prone to cause extrapyramidal side-effects than the oral form. ALAI has not been compared with other depots. Although the recommended starting dose is 400 mg, it is likely that there will be significant inter-individual dose variation. Dose optimisation in each patient will be necessary for best effectiveness and tolerability. ALAI is currently appropriate for aripiprazole-responsive patients who need a depot, but clinicians are likely to try ALAI in patients who have been on other depots, particularly in whom weight gain and hyperprolactinaemia have been problematic.